Bentonite gel as well as preparation method and application thereof
By adding grease and propylene carbonate to the bentonite gel and double modification, the problem of insufficient stability of bentonite gel is solved, and higher gel stability and application performance are achieved.
Patent Information
- Application Number
- CN202411624860.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
Bentonite gel has problems with insufficient stability in cosmetic applications, resulting in particle aggregation and oil output.
By adding an appropriate amount of grease and propylene glycol carbonate to the bentonite gel, and double modification is performed using titanate coupling agent and γ-aminopropyltriethoxysilane coupling agent to form an inorganic and organic modified layer. Enhance the stability and compatibility with oils and greases of bentonite particles.
It effectively avoids particle aggregation and oil production problems, improves the overall stability of the gel, and enhances its application performance in cosmetics.
Smart Images

Figure BDA0005134469080000071 
Figure BDA0005134469080000081
Abstract
Description
Technical Field
[0001] The present invention relates to the field of cosmetic ingredients, and more specifically, to a bentonite gel and a preparation method and application thereof. Background Art
[0002] As people's living standards improve and their health awareness increases, consumers are paying more and more attention to the quality and safety of cosmetics. They not only expect cosmetics to have good beauty effects, such as moisturizing, whitening, and concealing, but also require that the products are mild and non-irritating to the skin and do not contain harmful substances. The non-toxicity of bentonite makes it one of the ideal choices to meet this demand of consumers.
[0003] Bentonite is a clay mineral with montmorillonite as the main component. Its unique crystal structure gives it many excellent properties. Montmorillonite is a 2:1 layered silicate mineral composed of two layers of silicon-oxygen tetrahedrons sandwiched by one layer of aluminum-oxygen octahedron. This structure gives it a large specific surface area and ion exchange capacity, thus showing good adsorption properties. It can be used in combination with a variety of cosmetic components to meet the needs of diversified cosmetic functions and dosage forms while reducing the risk of adverse reactions to the skin, providing consumers with safer and more reliable cosmetic products.
[0004] However, bentonite gel still has the problem of insufficient stability in the application of cosmetics. Bentonite gel is a three-dimensional network structure system formed by bentonite particles dispersed in a solvent. In this system, the surface of bentonite particles is charged. Due to factors such as electrostatic effects, particles will aggregate. For example, when the electrolyte concentration in the system changes, the double layer on the surface of the bentonite particles will be compressed, reducing the electrostatic repulsion between the particles, making it easier for the particles to approach each other and aggregate. This aggregation will destroy the original network structure of the gel, resulting in a decrease in the stability of the gel. Since bentonite can absorb oil, if the stability of the gel system is insufficient, when external environmental factors such as pressure and temperature change, the oil will be squeezed or diffused out of the gel structure. Summary of the invention
[0005] In order to solve the problem of insufficient stability of bentonite gel in the current application of cosmetics, the present application provides a bentonite gel and a preparation method and application thereof.
[0006] In the first aspect, the bentonite gel provided in the present application adopts the following technical solution: A bentonite gel comprises 65-85 parts of oil, 12-22 parts of bentonite and 5-12 parts of propylene carbonate in parts by weight.
[0007] By adopting the above technical solution, oil plays an important role in lubrication and moisturizing in the gel system, and also integrates with other ingredients to form a stable structure. Bentonite is the main gel former, and its appropriate proportion can ensure the formation of a stable three-dimensional network structure. Propylene glycol carbonate helps to adjust the properties of the gel and enhance the binding force between the ingredients. The specific proportions in the present application scheme can effectively avoid these problems, improve the stability of the gel, prevent particle aggregation, and prevent oil leakage due to decreased stability.
[0008] Optionally, the oil includes one of cyclopentasiloxane, caprylic / caprylic triglyceride, hydrogenated polyisobutene, isododecane, and polydimethylsiloxane.
[0009] By adopting the above technical solution, these oils can interact well with bentonite particles to further improve the stability of the gel. The interaction between oils and bentonite can also adjust the viscosity and fluidity of the gel, making it more suitable for cosmetic application requirements.
[0010] Optionally, the bentonite is an organic-inorganic composite modified bentonite, and the organic-inorganic composite modified bentonite is doubly modified by a titanate coupling agent and a γ-aminopropyltriethoxysilane coupling agent.
[0011] Optionally, the preparation method of the organic-inorganic composite modified bentonite is: The titanate coupling agent and anhydrous ethanol were mixed in a mass ratio of 1:10, and stirred at room temperature to form a modified solution; The bentonite was dried and ground through a 200-mesh sieve, and the bentonite and the modified solution were mixed in a mass ratio of 1:(2.5-3.5), and stirred at 60-70°C for 3-4h; After the reaction is completed, a solid product is obtained by centrifugal separation, and the solid product is washed with anhydrous ethanol and dried to obtain an inorganic modified bentonite; Mix γ-aminopropyltriethoxysilane coupling agent and water in a mass ratio of 1:5, add acetic acid dropwise to adjust the pH value of the solution to 4-5, and stir at room temperature to form an organic modified solution; The inorganic modified bentonite and the organic modified solution are mixed in a mass ratio of 1:(1.5-2.5), stirred and reacted at 40-50°C for 4-5 hours. After the reaction is completed, the solid product is separated by filtration. The solid product is washed and dried to obtain an organic-inorganic composite modified bentonite.
[0012] By adopting the above technical scheme, an inorganic protective layer is first formed on the surface of bentonite particles through double modification with a titanate coupling agent and a γ-aminopropyl triethoxysilane coupling agent. The titanate coupling agent reacts with the hydroxyl groups on the surface of the bentonite particles to construct a solid inorganic coating layer on the surface of the particles, thereby enhancing the hardness and physical stability of the particles. This inorganic layer can effectively resist the influence of external factors such as temperature changes and pressure on the bentonite particles, reduce the crushing and structural deformation of the particles, and thus lay the foundation for the stability of the gel. Then, organic modification is performed, and the siloxane group of the γ-aminopropyl triethoxysilane coupling agent reacts with the hydroxyl groups on the surface of the inorganic modified layer. The organic groups extending outward make the bentonite have better hydrophobicity and compatibility with organic components. In the bentonite gel system, this good compatibility enables the modified bentonite particles to be more evenly dispersed in organic components such as oils and fats, reducing the aggregation between particles and further enhancing the stability of the gel.
[0013] In addition, the γ-aminopropyl triethoxysilane coupling agent gives bentonite hydrophobic organic groups, which can better interact with oil molecules and increase the binding force between the two. The modified bentonite can more effectively adsorb oil due to its special structure and surface properties. The inorganic modified layer and the organic modified layer work together to provide more adsorption sites and stronger adsorption force for oil molecules. This strong adsorption makes the oil more stable in the gel system and less susceptible to migration or separation due to external factors.
[0014] In a second aspect, the present application provides a method for preparing bentonite gel, using the following technical solution: A method for preparing bentonite gel comprises the following steps: The oil and bentonite are stirred at room temperature at a speed of 400-600 r / min for 15-30 minutes, and then propylene carbonate is added, and stirred at a speed of 1200-1600 r / min for 60-180 seconds until it becomes viscous, and the stirred product is ground to obtain bentonite gel.
[0015] By adopting the above technical scheme, by stirring grease and bentonite at room temperature at a speed of 400-600r / min for 15-30min, grease and bentonite can be preliminarily uniformly mixed, and grease can fully wrap bentonite particles to reduce the occurrence of local agglomeration. After adding propylene carbonate, the stirring speed is increased to 1200-1600r / min and stirred for 60-180s to a viscous state. The higher stirring speed can make propylene carbonate quickly dispersed in the mixed system of grease and bentonite, promoting the interaction between the three. Propylene carbonate, as an auxiliary agent, can adjust the properties of the gel. Under high-speed stirring, it can better combine with grease and bentonite to further optimize the uniformity of the system. Through the control of the conditions in the preparation process in this application, the formation and stability of the three-dimensional structural skeleton in the bentonite gel can be maximized. The product after stirring is ground so that the bentonite particles are more evenly dispersed in the gel system, reducing the agglomeration and size inhomogeneity of the particles. The method of the present application is short in time consumption and low in cost, and the operation process is relatively simple, which is very suitable for large-scale production. It has broad application prospects in the cosmetics, makeup and skin care industries.
[0016] Optionally, the grinding is performed using a three-roller mill, wherein the spacing between the front rollers of the three-roller mill is 7-10 μm, and the spacing between the rear rollers is 5-8 μm.
[0017] By adopting the above technical solution, during the three-roll mill grinding process, by setting the front roller spacing to 7-10μm and the rear roller spacing to 5-8μm, the bentonite gel will be subjected to strong extrusion and shear forces when passing through these two relatively small gaps, which can effectively break up the agglomerated particles in the gel and further refine the bentonite particles. After the three-roll mill grinding, the refinement and uniform distribution of the bentonite particles are conducive to forming a more stable three-dimensional network structure. Finer particles can better interweave with each other to form a tighter network, thereby enhancing the cohesion and stability of the gel.
[0018] Optionally, the grinding is repeated 1-2 times.
[0019] In a third aspect, the present application provides an application of bentonite gel, using the following technical solution: An application of bentonite gel, wherein the bentonite gel is applied in cream, lotion and facial mask.
[0020] By adopting the above technical solution, the bentonite gel of the present application can be used in creams, lotions and facial masks to enhance its stability, prevent oil-water separation, extend the shelf life, and improve the moisturizing and nourishing effects.
[0021] In summary, this application has the following beneficial effects: 1. Since the present application uses oil to exert lubrication and moisturizing effects and is integrated with other ingredients into a stable structure, bentonite is used as the main gel former to ensure a stable three-dimensional network structure in an appropriate proportion, and propylene carbonate adjusts the gel properties to enhance the binding force of the ingredients. This specific proportion can effectively avoid particle aggregation and oil leakage problems caused by decreased stability, thereby improving the overall stability of the gel.
[0022] 2. In the present application, it is preferred to perform double modification by titanate coupling agent and γ-aminopropyltriethoxysilane coupling agent. First, the titanate coupling agent reacts with the hydroxyl groups on the surface of bentonite particles to form an inorganic protective layer, thereby enhancing the hardness and physical stability of the particles, resisting the influence of external factors, and laying the foundation for the stability of the gel; then, the siloxane group of the γ-aminopropyltriethoxysilane coupling agent reacts with the hydroxyl groups of the inorganic modified layer to make the bentonite hydrophobic and compatible with organic components, so that the modified bentonite particles are more evenly dispersed in organic components such as oils and fats, reducing aggregation, and further enhancing the stability of the gel. The hydrophobic organic groups imparted thereto can also enhance the interaction and binding force with oil molecules, and the inorganic and organic modified layers jointly provide more adsorption sites and stronger adsorption force for oil molecules, making the oils and fats more stable in the gel system and not easily affected by external factors and migrate or separate.
[0023] 3. The method of the present application ensures the formation and stability of the three-dimensional structural skeleton of bentonite gel by controlling the preparation conditions. Grinding after stirring can make the bentonite particles more evenly dispersed and reduce agglomeration and heterogeneity. This method is time-saving, low-cost, and simple to operate. It is suitable for large-scale production and has broad application prospects in the cosmetics, makeup, and skin care industries. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0025] Preparation Example 1 Preparation of an organic-inorganic composite modified bentonite: Mix 1 kg of titanate coupling agent and 10 kg of anhydrous ethanol in a clean container and stir at room temperature for 30 minutes to fully dissolve the titanate coupling agent to form a uniform inorganic modified solution; The bentonite was dried at 110°C for 2 hours to remove the moisture therein, and then ground through a 200-mesh sieve. 1 kg of the bentonite was mixed with 3 kg of the inorganic modified solution, and stirred at 65°C for 4 hours. After the reaction is completed, the solid product is separated by centrifuging at a speed of 3000 r / min for 10 minutes, washed with anhydrous ethanol for 3 times to remove the unreacted modifier, and the washed solid product is dried at 85° C. for 8 hours to obtain inorganic modified bentonite; Mix 1 kg of γ-aminopropyltriethoxysilane coupling agent with 5 kg of deionized water, slowly drop 3% dilute acetic acid to adjust the pH value of the solution to 4-5, and stir evenly at room temperature to form an organic modified solution; 1 kg of inorganic modified bentonite was mixed with 2 kg of organic modified solution, and stirred at 45° C. for 5 hours. After the reaction was completed, the solid product was separated by filtration through a filter. The solid product was washed with deionized water and dried at 60° C. to obtain an organic-inorganic composite modified bentonite.
[0026] Preparation Example 2 Preparation of an inorganic composite modified bentonite: Mix 1 kg of titanate coupling agent and 10 kg of anhydrous ethanol in a clean container and stir at room temperature for 30 minutes to fully dissolve the titanate coupling agent to form a uniform inorganic modified solution; The bentonite was dried at 110°C for 2 hours to remove the moisture therein, and then ground through a 200-mesh sieve. 1 kg of the bentonite was mixed with 3 kg of the inorganic modified solution, and stirred at 65°C for 4 hours. After the reaction, the solid product was separated by centrifuge at 3000 r / min for 10 minutes, washed three times with anhydrous ethanol to remove the unreacted modifier, and the washed solid product was dried at 85° C. for 8 hours to obtain inorganic modified bentonite. Example
[0027] In this application, cyclopentasiloxane, caprylic acid / caprylic acid triglyceride, hydrogenated polyisobutylene, isododecane, and polydimethylsiloxane were purchased from MacLean Reagent, analytical grade. Bentonite was selected from MacLean Reagent B802109. Propylene carbonate was selected from Shanghai Jizhi Biochemical Technology Co., Ltd., analytical grade. Titanate coupling agent was selected from Hubei Longxin Chemical TMC-132. γ-Aminopropyl triethoxysilane coupling agent was selected from Merck Reagent, analytical grade.
[0028] Example 1 A method for preparing bentonite gel: 650g of oil and 120g of bentonite are added to a stirring tank. The oil is cyclopentasiloxane. Stir at 500r / min for 20min at room temperature. Then add 50g of propylene carbonate and stir at 1400r / min for 120s until it becomes viscous. Grind the stirred product using a three-roll mill with a front roller spacing of 7-10μm and a rear roller spacing of 5-8μm. Grind once to obtain bentonite gel.
[0029] Example 2 A method for preparing bentonite gel: 750g of oil and 180g of bentonite are added into a stirring tank, wherein cyclopentasiloxane is selected as the oil, and stirred at 500r / min for 20min at room temperature. Then 90g of propylene carbonate is added, and stirred at 1400r / min for 120s until it becomes viscous. The stirred product is ground using a three-roll mill, wherein the spacing between the front rollers is 7-10μm and the spacing between the rear rollers is 5-8μm. Grind once to obtain bentonite gel.
[0030] Example 3 A method for preparing bentonite gel: 850g of oil and 220g of bentonite are added to a stirring tank. The oil is cyclopentasiloxane. The mixture is stirred at 500r / min for 20min at room temperature. Then 120g of propylene carbonate is added. The mixture is stirred at 1400r / min for 120s until it becomes viscous. The stirred product is ground using a three-roll mill. The spacing between the front rollers in the three-roll mill is 7-10μm and the spacing between the rear rollers is 5-8μm. The mixture is ground once to obtain bentonite gel.
[0031] Example 4 A method for preparing bentonite gel: The difference from Example 2 is that the oil is caprylic acid / caprylic acid triglyceride.
[0032] Example 5 A method for preparing bentonite gel: The difference from Example 2 is that the oil is hydrogenated polyisobutylene.
[0033] Example 6 A method for preparing bentonite gel: The difference from Example 2 is that isododecane is used as the oil.
[0034] Example 7 A method for preparing bentonite gel: The difference from Example 2 is that the oil is polydimethylsiloxane.
[0035] Example 8 A method for preparing bentonite gel: The difference from Example 2 is that 750g of oil and 180g of bentonite are added to a stirring tank, the oil is cyclopentasiloxane, and stirring is carried out at room temperature at a speed of 500r / min for 15min.
[0036] Example 9 A method for preparing bentonite gel: The difference from Example 2 is that 750g of oil and 180g of bentonite are added to a stirring tank, the oil is cyclopentasiloxane, and stirring is carried out at room temperature at a speed of 500r / min for 30min.
[0037] Example 10 A method for preparing bentonite gel: The difference from Example 2 is that the gel is stirred at a speed of 1200 r / min for 120 s until it becomes viscous.
[0038] Embodiment 11 A method for preparing bentonite gel: The difference from Example 2 is that the gel is stirred at a speed of 1600 r / min for 120 s until it becomes viscous.
[0039] Example 12 A method for preparing bentonite gel: The method is different from Example 2 in that the gel is ground twice using a three-roll mill.
[0040] Example 13 A method for preparing bentonite gel: The difference from Example 2 is that the spacing between the front rollers in the three-roller mill is 4-7 μm, and the spacing between the rear rollers is 2-5 μm.
[0041] Embodiment 14 A method for preparing bentonite gel: The difference from Example 2 is that the spacing between the front rollers in the three-roller mill is 10-13 μm, and the spacing between the rear rollers is 8-11 μm.
[0042] Embodiment 15 A method for preparing bentonite gel: The difference from Example 2 is that the bentonite is organic-inorganic composite modified bentonite, which is prepared by Preparation Example 1.
[0043] Comparative Example Comparative Example 1 A method for preparing bentonite gel: The difference from Example 2 is that propylene carbonate is replaced by an equal mass of propylene glycol.
[0044] Comparative Example 2 A method for preparing bentonite gel: The method is different from Example 2 in that no grinding treatment is performed.
[0045] Comparative Example 3 A method for preparing bentonite gel: The difference from Example 15 is that the bentonite is inorganic composite modified bentonite, which is prepared by Preparation Example 2.
[0046] Performance testing Detection Methods 50 g of sample was taken from each of the bentonite gels prepared above, and the viscosity was tested using a viscometer at 50° C. and 50% humidity. The sample was retested after 7 days, 30 days, and 90 days to judge the stability of the bentonite gel based on the change in viscosity.
[0047] Table 1 Test data statistics Combining Example 2 and Comparative Examples 1-2 with Table 1, it can be seen that the propylene carbonate in the present application helps to adjust the properties of the gel and enhance the binding force between the components. After grinding with a three-roll mill, the refinement and uniform distribution of the bentonite particles are conducive to forming a more stable three-dimensional network structure. Finer particles can better interweave with each other to form a tighter network, thereby enhancing the cohesion and stability of the gel.
[0048] Combining Examples 2, 15 and Comparative Example 3 with Table 1, it can be seen that through dual modification with titanate coupling agent and γ-aminopropyltriethoxysilane coupling agent, the inorganic layer can effectively resist the influence of external factors such as temperature change, pressure, etc. on bentonite particles, and the organic modification makes the bentonite have better hydrophobicity and compatibility with organic components. In the bentonite gel system, this good compatibility enables the modified bentonite particles to be more evenly dispersed in organic components such as oils and fats, reducing the aggregation between particles and further enhancing the stability of the gel.
[0049] It can be seen from Examples 1-3 and Table 1 that the specific ratios in the present application can effectively avoid these problems, improve the stability of the gel, prevent particle aggregation, and prevent oil leakage due to decreased stability.
[0050] Combining Example 2 and Examples 4-7 with Table 1, it can be seen that these oils can interact well with bentonite particles to further improve the stability of the gel. The interaction between oils and bentonite can also adjust the viscosity and fluidity of the gel, making it more suitable for the application requirements of cosmetics.
[0051] In combination with Example 2 and Example 8-14 and in combination with Table 1, it can be seen that by stirring grease and bentonite at a speed of 400-600r / min for 15-30min at room temperature, grease and bentonite can be preliminarily uniformly mixed, and grease can fully wrap bentonite particles to reduce the occurrence of local agglomeration. After adding propylene carbonate, the stirring speed is increased to 1200-1600r / min and stirred for 60-180s to a viscous state. The higher stirring speed enables propylene carbonate to be rapidly dispersed in the mixed system of grease and bentonite, promoting the interaction between the three. Through the control of the conditions in the preparation process in this application, the formation and stability of the three-dimensional structural skeleton in the bentonite gel can be maximized. During the three-roller mill grinding process, by setting the front roller spacing to 7-10μm and the rear roller spacing to 5-8μm, the bentonite gel will be subjected to strong extrusion and shearing forces when passing through these two relatively small gaps, and the agglomerated particles in the gel can be effectively broken, so that the bentonite particles are further refined.
[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A bentonite gel, characterized in that: The components thereof include 65-85 parts of oil, 12-22 parts of bentonite and 5-12 parts of propylene carbonate by weight.
2. The bentonite gel according to claim 1, characterized in that: The oil comprises one of cyclopentasiloxane, caprylic / capric triglyceride, hydrogenated polyisobutene, isododecane and polydimethylsiloxane.
3. The bentonite gel according to claim 1, characterized in that: The bentonite is organic-inorganic composite modified bentonite, and the organic-inorganic composite modified bentonite is double-modified by a titanate coupling agent and a γ-aminopropyltriethoxysilane coupling agent.
4. The bentonite gel according to claim 3, characterized in that: The preparation method of the organic-inorganic composite modified bentonite is: The titanate coupling agent and anhydrous ethanol were mixed in a mass ratio of 1:10, and stirred at room temperature to form a modified solution; The bentonite was dried and ground through a 200-mesh sieve, and the bentonite and the modified solution were mixed in a mass ratio of 1:(2.5-3.5), and stirred at 60-70°C for 3-4h; After the reaction is completed, a solid product is obtained by centrifugal separation, and the solid product is washed with anhydrous ethanol and dried to obtain an inorganic modified bentonite; Mix γ-aminopropyltriethoxysilane coupling agent and water in a mass ratio of 1:5, add acetic acid dropwise to adjust the pH value of the solution to 4-5, and stir at room temperature to form an organic modified solution; The inorganic modified bentonite and the organic modified solution are mixed in a mass ratio of 1:(1.5-2.5), stirred and reacted at 40-50°C for 4-5 hours. After the reaction is completed, the solid product is separated by filtration. The solid product is washed and dried to obtain an organic-inorganic composite modified bentonite.
5. A method for preparing bentonite gel according to any one of claims 1 to 4, characterized in that: The following steps are involved: The oil and bentonite are stirred at room temperature at a speed of 400-600 r / min for 15-30 minutes, and then propylene carbonate is added, and stirred at a speed of 1200-1600 r / min for 60-180 seconds until it becomes viscous, and the stirred product is ground to obtain bentonite gel.
6. The bentonite gel according to claim 5, characterized in that: The grinding is performed using a three-roller mill, wherein the spacing between the front rollers of the three-roller mill is 7-10 μm, and the spacing between the rear rollers is 5-8 μm.
7. The bentonite gel according to claim 5, characterized in that: The grinding was repeated 1-2 times.
8. An application of the bentonite gel according to claim 1, characterized in that: The bentonite gel is applied in creams, lotions and facial masks.
Citation Information
Cited By
Bentonite gel, preparation method therefor, and use thereof
WO2026103296A1